Phrenic nerve stimulation as a novel therapeutic approach for heart failure with central sleep apnea: a systematic review - Alverina, Clara; Kamila, Rizqi Apsari Fairuz; Rifa’I, Alfiani Zukhruful Fitri (The Indonesian Heart Association, 2025)
Introduction: Heart failure (HF) is a chronic condition associated with significant morbidity and mortality. Phrenic nerve stimulation (PNS) has emerged as a novel therapeutic approach aimed at improving outcomes in patients with heart failure, particularly those suffering from central sleep apnea (CSA). Objectives: This study aims to evaluate the efficacy and safety of PNS in HF patients with CSA, especially its impact on reducing CSA severity and improving the apnea-hypopnea index (AHI) and left ventricular ejection fraction (LVEF). Methods: A comprehensive search was conducted across multiple databases including Pubmed, Web of Science, Science Direct, and ProQuest, following PRISMA guidelines. The search strategy used the MeSH keywords (phrenic nerve stimulation) AND (heart failure). Inclusion criteria encompassed studies published in 2014 - 2023 that evaluated the effects of PNS on patients with HF and reported on relevant clinical outcomes. After a thorough screening process, five studies were identified as relevant and included in the review. Data extraction and quality assessment were independently conducted by three reviewers, with results synthesized using a systematic approach. The quality of the included studies was assessed using the Newcastle-Ottawa Scale (NOS). The research protocol was registered at PROSPERO (ID: CRD42024604614). Results: The studies reviewed demonstrated that PNS significantly reduces the central apnea index (CAI), AHI and improves sleep quality in heart failure patients. Moreover, improvements in LVEF and reductions in heart failure-related hospitalizations were observed. Patient satisfaction was generally high, and adverse events were minimal, suggesting that PNS is a safe and effective treatment option for HF patients especially those suffering from CSA. Conclusion: Phrenic nerve stimulation presents a promising therapeutic option for improving cardiac and sleep outcomes in heart failure patients. Further large-scale, randomized controlled trials are warranted to establish the long-term efficacy and safety of PNS in this population.